Плазмонні резонанси складних наноструктур - Ілляшенко, Л. М. (My University, 2012)
В роботі досліджені особливості поширення, розсіювання та поглинання електромагнітних хвиль в нових нанотехнологічних структурах для створення сучасних оптичних приладів та пристроїв, принцип дії яких будується на використанні плазмонних резонансів, а також взаємодії електромагнітних полів діелектричних, напівпровідникових та плазмонних структурних елементів. Зроблено висновок про необхідність створення спектральних методів граничних інтегральних рівнянь для обчислення характеристик дальнього та ближнього електромагнітного поля в широкій смузі довжин хвиль збудження в залежності від геометричних та матеріальних параметрів кожного компоненту наносистем та їх структурних особливостей. На основі спектрального методу Фур'є-Гальоркіна розроблені чисельно-аналітичні схеми, що реалізовані у прикладних програмах, та дозволили розв'язати зазначені актуальні задачі та чисельно обґрунтувати експоненціальну збіжність розв'язку. This thesis is devoted to study of electromagnetic wave propagation, scattering and absorption in new nanotechnological structures for design of novel optical devices. This research is driven by the desire of optical device miniaturization exploiting plasmon resonances and various coupling induced effects for electromagnetic fields of their structural details, including dielectric, semiconductors and plasmonic nanoparticles. To solve challenging problems, conclusions about needs to develop new Spectral Boundary Integral Equation (BIE) methods for efficient calculations of far- and near-field characteristics in wide spectrum of electromagnetic wavelengths are made after the review of literature. Development of new spectral Fourier-Galerkin algorithms and their implementation in novel numerical simulation tool is conducted. All possible geometrical configurations of plasmonic nanorods, including periodic and aperiodic structures of homogeneous and layered nanoparticles are considered based on the same approach, that lead to solving the Maxwell's equations with material properties presented by frequency dependent complex valued dielectric permittivity. Novel technique of parameterization for boundaries to be used in conjunction with spectral Fourier methods is invented. The use of parameterizations allows converting the BIE along arbitrary curve to BIE over a circle, so that Fourier harmonics provide basis for their discretization. It also permits regularization of integral kernels using a singularity subtraction technique, leading to integrals with smooth kernels to be evaluated by Fast Fourier Transforms (FFT). These techniques also convert all equations to the Fredholm equations of the second kind for which a numerical stability is guaranteed. Exponential convergence rate of results is proved. Therefore, all algorithms developed in this work may be seen as FFT enhanced spectral Fourier Galerkin methods for parameterized BIE with singularity subtraction. Code validation was done through the comparison with results of BEM, presented in literature, and numerical results for testing cases obtained with FEM, FDTD, MAS and MMP, that were also validated through the comparison with results of experimental research. The set of numerical experiments clearly demonstrates performances of developed BIE tool, that allows to solve a lot of new challenging problems. The dependence of resonating wavelength on various parameters, including shape, size, material properties and coupling induced properties of nanodetails, such as interparticle distance, orientation, and position of the light source in novel configurations was found. This permits adjusting the mentioned above parameters in the most beneficial way to make it possible to build novel devices with dramatically improved performance covering a wide range of desired properties.
Keywords: плазмонні резонанси; складні наноструктури; ефекти взаємодії електромагнітних полів нанодеталей структури; дисперсія матеріалів; спектральні методи Граничних Інтегральних Рівнянь; plasmon resonances; complex nanostructures; coupling-induced; electromagnetic effects; dispersive materials; spectral boundary integral equation methods